ANALISIS PERBANDINGAN KINERJA KEUANGAN PERBANKAN SYARIAH DENGAN PERBANKAN KONVENSIONAL - Setyaningsih, Ari -; Utami, Setyaningsih Sri (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2013)
ABSTRACT Methods This study uses a case study on PT Bank Syariah Muamalat Tbk and PT Bank BRI Tbk is listed on the Indonesia Stock Exchange. Data sources using secondary data obtained from the financial statements of PT Bank Syariah Muamalat Tbk and PT Bank BRI Tbk, published in the period 2009 – 2011. Data collection techniques using documentation and literature. Analysis using financial ratio analysis of CAR, NPL, ROA, BOPO and LDR. The results that: CAR ratio at PT Bank BRI Tbk look better than the PT Bank Syariah Muamalat Indonesia Tbk. This is indicated by the higher value of CAR for the period 2009 – 2011 which is owned by PT Bank BRI Tbk. NPL ratio at PT Bank Syariah Muamalat Indonesia Tbk better than the PT Bank BRI Tbk. This is indicated by the lower value of NPL during the period 2009 – 2011. ROA ratio at PT Bank BRI Tbk look better than the PT Bank Syariah Muamalat Indonesia Tbk. This is indicated by the higher value of ROA over the period 2009 – 2011. BOPO ratio at PT Bank BRI Tbk better than the PT Bank Syariah Muamalat Indonesia Tbk. This is indicated by the lower value of BOPO over the period 2009 – 2011. Liquidity ratio at PT Bank BRI Tbk better than financial performance compared with PT Bank Syariah Muamalat Indonesia Tbk. This is shown both on the value of LDR. During the period 2009 – 2011 the value of LDR at PT Bank BRI Tbk lower. Keywords: CAR, NPL, ROA, BOPO and LDR